SOME PROBLEMS OF EXPLICIT SIGNS OF LEGALIZATION (LAUNDERING) OF CRIMINALLY OBTAINED PROPERTY COMMITTED WITH THE USE OF VIRTUAL ASSETS (Bulletin of criminological association of Ukraine, 2024)
The article examines the peculiarities of the impact of technical, legal, financial and economic properties of virtual assets on the content of explicit features of a criminal offence under Article 209 of the Criminal Code of Ukraine. The author notes the problems of recognising virtual assets as the subject of legalisation (laundering) of property and funds obtained by criminal means. The author examines the peculiarities of legal regulation of virtual assets under Ukrainian legislation. It is concluded that due to the amendments to the Civil Code of Ukraine in 2023 in terms of regulating the legal status of property, it became possible to recognise virtual assets as the subject of a criminal offence when qualifying it under Article 209 of the Criminal Code of Ukraine. The author assesses the prospects of recognising virtual assets as an object of a criminal offence under Article 209 of the Criminal Code of Ukraine after the entry into force of the Law ‘On Virtual Assets’.
Keywords: corpus delicti of a criminal offence; implicit signs of corpus delicti of a criminal offence; legalisation of the proceeds of crime; virtual assets; subject matter of a criminal offence; blanket disposition